DETERMINATION OF CAUSES OF MENSTRUAL DISORDERS USING PALM COEIN CLASSIFICATION SYSTEM - Karim, Rukhsana; Saima Ayub (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the causes of menstrual disorders according to PALM-COEIN classification system by international federation of gynecology and obstetrics (FIGO). Methodology: This descriptive study was conducted in Department of Obstetrics & Gynaecology, Hayatabad Medical Complex, Peshawar, from 8th August 2019 to 9th August 2020. Patients admitted for hysterectomy/ endometrial sampling due to abnormal uterine bleeding (AUB) were included in the study through non-probability convenient sampling. Detailed history, clinical examination and relevant investigations were recorded on a predesigned proforma. Abnormal uterine bleeding was then classified according to FIGO new system (PALM-COEIN). Descriptive statistics were used in the form of frequencies and percentages. Results: A total of 78 patients underwent surgical intervention for abnormal uterine bleeding. The mean age of the participants was 44.0±3.9 years. Most of the patients were either multi or grand multipara (n=75, 96.2%). Majority reported to have regular bleeding (n=55, 70.5%), frequent cycles (n=56,71.8%), prolonged flow (n=54, 69.2%) and heavy blood loss (n=61,78.2%). The PALM portion comprised of 33 (42.3%) causes of AUB, while COEIN portion comprises of 29 (37.2%) causes while sixteen (20.5%) cases were having more than one underlying pathologies. AUB-L (Leiomyoma) was most common cause in the PALM group (n=13, 16.7%), while AUB-E (Endometrial) in the COEIN group (n=13, 16.7%). Conclusion: Multiple/mixed etiologies were the most common causes of AUB, followed by AUB-L and AUB-E.